2012
DOI: 10.1246/cl.2012.1178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SDS and CTAB on Derivatives of Antimicrobial Peptides Arenicin and LL-37

Abstract: The interaction of two antimicrobial peptides (AMPs) with amphiphiles was investigated. In addition, the influence of sodium dodecyl sulfate (SDS) and cetyltrimethylammonium bromide (CTAB) solutions, both below and above the critical micelle concentration (cmc), was investigated by circular dichroism (CD) spectroscopy. The AMPs we used were from two different classes: C/S-Ar-1, from a lugworm, and LL-20, a fragment of human LL-37. Cationic CTAB did not influence the AMPs, independent of the amphiphile aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…On the other hand, it was the unique characteristic of P1 to maintain its original structure. AMPs (arenicin, LL-37, and RR12) adopted a predominant β-strand or random coil structure in an aqueous solution, but they underwent a conformational change with an increase in α-helix when complexed with SDS ( Dannehl, Travkova & Brezesinski, 2012 ; Krenev et al, 2020 ; Wu et al, 2020 ). In addition, some peptides (OM19R analogs) had the characteristics of random coil, and their structures did not significantly change in the presence of SDS, supporting that AMP-facilitated intracellular activities (increased DNA binding, reduced synthesis of intracellular proteins, and decreased intracellular ATP) influenced a microbial inhibition rather than membrane disintegration ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was the unique characteristic of P1 to maintain its original structure. AMPs (arenicin, LL-37, and RR12) adopted a predominant β-strand or random coil structure in an aqueous solution, but they underwent a conformational change with an increase in α-helix when complexed with SDS ( Dannehl, Travkova & Brezesinski, 2012 ; Krenev et al, 2020 ; Wu et al, 2020 ). In addition, some peptides (OM19R analogs) had the characteristics of random coil, and their structures did not significantly change in the presence of SDS, supporting that AMP-facilitated intracellular activities (increased DNA binding, reduced synthesis of intracellular proteins, and decreased intracellular ATP) influenced a microbial inhibition rather than membrane disintegration ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same holds for DOPC monolayers. Obviously, LL-20 cannot penetrate into zwitterionic lipid monolayers at physiologically relevant surface pressures (30)(31)(32)(33)(34)(35) mN/m), independent of the lipid phase. LL-32 has a slightly higher MIP of (35 2)mN/m into DPPC with a slope of −0.7, indicating an interaction with the zwitterionic DPPC at low lateral pressures.…”
Section: Interactions Of Ll-32 and Ll-20 With Pre-compressed Monolayersmentioning
confidence: 99%
“…It was shown that the peptides differ drastically in their surface activity (equilibrium adsorption pressure). As concluded from CD spectra, both peptides are unstructured in bulk but exhibit different secondary structures when adsorbed to the air/buffer interface [31,32]. While LL-32 transforms into an -helix lying flat at the buffer surface, with a helix diameter of 17 Å, LL-20 adopts a partly unstructured conformation.…”
Section: Introductionmentioning
confidence: 95%